Fabrication of green device for efficient capture of toxic methylene blue from industrial effluent based on K2Zn3[Fe(CN)6]2·9H2O nanoparticles reinforced gum xanthan-psyllium hydrogel nanocomposite. Issue 4 (1st October 2016) - Kaith, B. S.; Sharma, Jitender; Sukriti,; Sethi, Surbhi; Kaur, Tajinder; Shanker, Uma; Jassal, Vidhisha
Abstract : In the present work, the synthesis of novel device for the efficient removal of toxic cationic dye methylene blue (MB) from aqueous fluid was carried out. The device was fabricated by in-situ incorporation of K2 Zn3 [Fe(CN)6 ]2 ·9H2 O nanoparticles into gum semi-IPN matrix in the presence of glutaraldehyde-ammonium persulphate as crosslinker–initiator system. The effect of several reaction variables such as time, solvent, temperature, pH, crosslinker, initiator concentration and monomer concentration on the fluid uptake capacity of the candidate sample was explored. The morphological and structural properties were studied using Fourier transform infrared spectroscopy, scanning electron microscopy, transmission electron microscopy and X-ray diffraction studies. Thermal stability was evaluated by thermogravimetric analysis/differential thermal analysis/differential thermogravimetric analysis. Contact time, adsorbent dose and initial concentration of dye solution were optimized for maximum dye removal and it was observed that nanocomposite could effectively remove 94.5% of MB dye. Langmuir and Freundlich adsorption isotherms were studied which showed a good applicability to the adsorption process of MB onto the nanocomposite with maximum adsorption efficiency of 1.878 mg g −1 . The nanocomposite designed by green synthetic route was found to be eco-friendly and biodegradable, so the principle of green chemistry was followed. Abstract :